Moral Scens from Urban Life: Moral Perception of Modernity in Imperial Brazil - Narita, Felipe Ziotti (Praktyka Teoretyczna, 2017)
In this article, I analyze moral perceptions of modernity in Rio de Janeiro between the 1850s and 1860s. Against a long theoretical tradition in the Latin American social sciences that emphasizes nineteenth-century modernity in the region as an opaque process (a mere attempt at imitating the Western European “pure” model), I would like to follow another theoretical path; that is, my analysis focuses on tangible experiences of modernity during the apogee of the Brazilian Empire. This research looks to newspapers, schoolbooks, books, and speeches delivered by the cultural elite in the public sphere. I analyze how moral perceptions of urban life in nineteenth-century Rio de Janeiro can be articulated into a structure based on processes of education. In other words, beyond the materiality in urban space (public street lighting, oil and gas companies, urban cleanliness, public gardens, etc.), there is an implicit relationship between the inner problems (political turbulence, poverty, and moral management of the urban population) and the moral content of modernity (which can be understood in terms of structural prescriptions). These processes of education, instead of an institution-centered practice concentrated only on schools, elaborate a diffuse set of prescriptions whose nexus is constituted by the content of morality. The paper reflects on the conditions of production and reproduction of modernity in a peripheral area (former colonial space) in the nineteenth century.